Using Experimental Paradigms to Examine Alcohol's Role in Men's Sexual Aggression: Opportunities and Challenges in Proxy Development. (August 2015) - Abbey, Antonia; Wegner, Rhiana
The goals of this article are to review the major findings from alcohol administration studies that use sexual aggression proxies and to encourage additional experimental research that evaluates hypotheses about the role of alcohol in the etiology of men's sexual aggression. Experiments allow participants to be randomly assigned to drink conditions, therefore ensuring that any differences between drinkers and nondrinkers can be attributed to their alcohol consumption. One of the biggest challenges faced by experimental researchers is the identification of valid operationalizations of key constructs. The tension between internal and external validity is particularly problematic for violence researchers because they cannot allow participants to engage in the target behavior in the laboratory. The strengths and limitations associated with written vignettes, audiotapes, videotapes, and confederate proxies for sexual aggression are described. Suggestions are made for future research to broaden the generalizability of the findings from experimental research.